Analisis Spasial Pertumbuhan Inklusif Kabupaten/Kota Di Sulawesi Tengah Tahun 2015-2020 - Fadhel Imam Haichal Tanjung; Ernawati Pasaribu (Politeknik Statistika STIS, 2022)
Central Sulawesi province is the province which has the third highest economic growth in Indonesia during 2015-2020. However, high economic growth is not in line with solving problems such as the high percentage of the poor, income inequality, and open unemployment. Based on this, indicators are needed that can be a measure of the success of economic development through inclusive growth. Therefore, this study aims to describe the level of inclusive growth using the inclusive index (II) by Ramos, Ranieri, and Lammens and to find out the factors that influence it in districts/cities in Central Sulawesi. In addition, this study also identifies the spatial interrelationships of inclusive growth. The results show that inclusive growth has increased in the 2015-2020 period. Based on the spatial panel method, with spatial lag fixed effect, obtained positive spatial autocorrelation results. There is a positive and significant influence between Road Infrastructure, Government spending on social protection functions, Processing Industry and Electricity Access on inclusive growth. Government spending on education and access to clean water has a negative and significant impact on inclusive growth